1994
DOI: 10.1093/ageing/23.6.465
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression in Geriatric Medical Outpatients

Abstract: One hundred and fifty-nine patients attending a geriatric medical outpatient clinic were screened for depression using the geriatric depression scale (GDS) and brief assessment schedule depression cards (BASDEC). Twenty-two (13.8%) patients screened positive with one or other test, 13 (8.2%) being positive with both screening tests. There was a highly significant correlation between the two screening tests but the BASDEC instrument was quicker and easier to administer. Eighteen of 22 patients who screened as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
9
2
Order By: Relevance
“…In some studies of medically hospitalised patients, elderly people with somewhat reduced cognitive functioning have been excluded (Koenig, George, Peterson, & Pieper, 1997;Koenig, Meador, Cohen, & Blazer, 1988;McCrea, Arnold, Marchevsky, & Kaufman, 1994). In this study, we included the patients as long as they did not have severe dementia (CDR ¼ 3) (Morris, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies of medically hospitalised patients, elderly people with somewhat reduced cognitive functioning have been excluded (Koenig, George, Peterson, & Pieper, 1997;Koenig, Meador, Cohen, & Blazer, 1988;McCrea, Arnold, Marchevsky, & Kaufman, 1994). In this study, we included the patients as long as they did not have severe dementia (CDR ¼ 3) (Morris, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The GDS includes a screening questionnaire for depression and anxiety. The total scores range from 0 to 15, with higher scores indicating more severe symptoms of depression (14,15). The AS scores range from 0 to 42, with higher scores indicating more severe apathy.…”
Section: Standard Cognitive and Affective Assessmentsmentioning
confidence: 99%
“…It has shown a very good sensitivity (>0.80), specificity (>0.90), and accuracy in predicting clinical results of medically ill elderly patients 79. Both GDS and BASDEC are not time-consuming to administer, and they are relatively free of somatic symptoms 80. Adshead et al78 showed that agreement between the 2 scales was high.…”
Section: Screening and Evaluation Of Psdmentioning
confidence: 99%
“…Adshead et al78 showed that agreement between the 2 scales was high. However, McCrea et al80 found that BASDEC was easier to administer. In a systematic review, Hackett and Anderson64 recommended that the gold standard method for diagnosis PSD is using a semistructured psychiatric interview, which meets all the standards needed for a specific diagnostic criterion (such as DSM criteria or International Classification of Diseases).…”
Section: Screening and Evaluation Of Psdmentioning
confidence: 99%